Entropy generation for forced convection in a porous saturated circular tube with uniform wall temperature - Hooman, K.; Ejlali, A. (International communications in heat and mass transfer, 2007)
A numerical study is reported to investigate both the First and the Second Law of Thermodynamics for thermally developing forced convection in a circular tube filled by a saturated porous medium, with uniform wall temperature, and with the effects of viscous dissipation included. A theoretical analysis is also presented to study the problem for the asymptotic region applying the perturbation solution of the Brinkman momentum equation reported by (K. Hooman, K., A.A. Ranjbar-Kani, A perturbation based analysis to investigate forced convection in a porous saturated tube, Journal of Computational and Applied Mathematics 162 (2) (2004) 411–419.). Expressions are reported for the temperature profile, the Nusselt number, the Bejan number, and the dimensionless entropy generation rate in the asymptotic region. Numerical results are found to be in good agreement with theoretical counterparts.